The integrase of genomic island GIsul2 mediates the mobilization of GIsul2 and ISCR-related element CR2-sul2 unit through site-specific recombination - Zhang, Gang; Cui, Qinna; Li, Jianjuan; Guo, Ruiliang; Leclercq, Sébastien Olivier; Du, Lifeng; Tang, Na; Song, Yuqin; Wang, Chao; Zhao, Fangqing; Feng, Jie (Frontiers in Microbiology, 2022)
In the worldwide health threat posed by antibiotic resistant bacterial pathogens, mobile genetic elements (MGEs) play a critical role in favoring the dissemination of resistance genes. Among them, genomic island GIsul2 and ISCR-related element CR2-sul2 unit are believed to participate in this dissemination. However, the mobility of the two elements has not yet been demonstrated. Here, we found that GIsul2 and CR2-sul2 unit can excise from the host chromosomal attachment site (attB) in Shigella flexneri. Through establishing a two-plasmid mobilization system composed of donor plasmid bearing the GIsul2 and trap plasmid harboring the attB in recA-deficient Escherichia coli, we reveal that the integrase of GIsul2 can perform the excision and integration of GIsul2 and CR2-sul2 unit by site-specific recombination between att core sites. Furthermore, we demonstrate that the integrase and the att sites are required for mobility through knockout experiments. Our findings provide the first experimental characterization of the mobility of GIsul2 and CR2-sul2 unit that mediated by integrase. They also suggest a potential and unappreciated role of GIsul2 integrase family in the dissemination of CR2-sul2 units carrying various resistance determinants in between.